56t-14=1

Combine 56 and t.

5t6-14=1

Add 14 to both sides of the equation.

5t6=1+14

Add 1 and 14.

5t6=15

5t6=15

Multiply both sides of the equation by 65.

65⋅5t6=65⋅15

Simplify 65⋅5t6.

Cancel the common factor of 6.

Cancel the common factor.

65⋅5t6=65⋅15

Rewrite the expression.

15⋅(5t)=65⋅15

15⋅(5t)=65⋅15

Cancel the common factor of 5.

Factor 5 out of 5t.

15⋅(5(t))=65⋅15

Cancel the common factor.

15⋅(5t)=65⋅15

Rewrite the expression.

t=65⋅15

t=65⋅15

t=65⋅15

Simplify 65⋅15.

Cancel the common factor of 5.

Factor 5 out of 15.

t=65⋅(5(3))

Cancel the common factor.

t=65⋅(5⋅3)

Rewrite the expression.

t=6⋅3

t=6⋅3

Multiply 6 by 3.

t=18

t=18

t=18

Solve for t 5/6t-14=1